The blackwell companion to sociology of religion - Fenn, Richard K. (Malden Blackwell Publishing Ltd., 2001)
The Blackwell Companion to Sociology of Religion is presented in three comprehensive parts. Written by a range of outstanding academics, the volume explores the current status of the sociology of religion, and how it might look in future.